Comment la connaissance de la diversité posturo-locomotrice des primates a-t-elle transformé la compréhension de celle des hominines ? - Mathilde Lequin; François Marchal (Revue de Primatologie)
In recent decades, the way paleoanthropologists conceive of bipedalism has changed considerably. If bipedalism was once thought to be a unique characteristic, specific to the hominin lineage and marking its origin, the hypothesis of its anatomical and behavioral diversity, envisaged since the 1960s, is now widely accepted. With a history and philosophy of science angle, this article aims to analyze the contribution of primatology to the transformation of the theoretical framework used in paleoanthropology to think about the evolution of bipedalism. While fossil discoveries are often presented as the driving force of theoretical change in this discipline, we show that studies on primate locomotor diversity have also played a fundamental role in deconstructing certain interpretative schemes frequently used in the analysis of hominin fossil remains. Through our epistemological approach, we show how the innovative methodologies used in primatology can constitute conceptual and analytical tools that can be mobilized in paleoanthropology. These tools make it possible to free this field from a certain anthropocentrism based on the equivalence between biped and hominin and consequently to propose new hypotheses concerning the origin and evolution of bipedalism.